Effect of Angle of Attack on Pressure and Lift Coefficient of ONERA OA206 Wing Model Using Computational Fluid Dynamics Method - Anggraeni, Resti (Computational And Experimental Research In Materials And Renewable Energy, 2019)
In this study, we computed the lift force of the aircraft with ONERA OA206 airfoil type. It was positioned at 0%, 25%, 50%, 75%, and 100% of the wingspan for Angle of Attack (AoA) variations of 0o, 4o, 8o, 12o, and 16o. The research was to determine the effect of AoA on pressure, pressure coefficient (Cp), and lift coefficient (CL) on the ONERA OA206 aircraft wing. It shows that the greater AoA on the result of the pressure contour causes the increase in the difference of span at AoA 0o to 16o t these are 0.25%; 0.26%; 0.43%; 0.52%; and 0.53%. Through the graph of the pressure coefficient (Cp) against x/c, it can be seen that the greater AoA, the expansion point, and the stagnation point will shift to the right with the direction of x/c. In addition, the Cp at the lower is greater than the upper of the airfoil. Based on the research results, it was found that CL at the position of 0% to 50% increased when given AoA from 0o to 12o (CL max) and decreased at AoA = 16o (stall). Meanwhile, CL at 75% to 100% increased when given AoA from 0o to 8o (CL max) and decreased at AoA = 12o (stall). With these results, it can be concluded that the maximum AoA that can be applied to the wing of the ONERA OA206 aircraft is 8o. The closer to the end position of the airfoil, the higher the CL measured.